The role of feedback in emergency ambulance services: a qualitative interview study - Caitlin Wilson; Anne-Marie Howell; Gillian Janes; Jonathan Benn (BMC, 2022)
Abstract Background Several international studies suggest that the feedback that emergency ambulance service (EMS) personnel receive on the care they have delivered lacks structure, relevance, credibility and routine implementation. Feedback in this context can relate to performance or patient outcomes, can come from a variety of sources and can be sought or imposed. Evidence from health services research and implementation science, suggests that feedback can change professional behavior, improve clinical outcomes and positively influence staff mental health. The current study aimed to explore the experience of EMS professionals regarding current feedback provision and their views on how feedback impacts on patient care, patient safety and staff wellbeing. Methods This qualitative study was conducted as part of a wider study of work-related wellbeing in EMS professionals. We used purposive sampling to select 24 frontline EMS professionals from one ambulance service in the United Kingdom and conducted semi-structured interviews. The data was analyzed in iterative cycles of inductive and deductive reasoning using Abductive Thematic Network Analysis. The analysis was informed by psychological theory, as well as models from the wider feedback effectiveness and feedback-seeking behavior literature. Results Participants viewed current feedback provision as inadequate and consistently expressed a desire for increased feedback. Reported types of prehospital feedback included patient outcome feedback, patient-experience feedback, peer-to-peer feedback, performance feedback, feedforward: on-scene advice, debriefing and investigations and coroners' reports. Participants raised concerns that inadequate feedback could negatively impact on patient safety by preventing learning from mistakes. Enhancing feedback provision was thought to improve patient care and staff wellbeing by supporting personal and professional development. Conclusions In line with previous research in this area, this study highlights EMS professionals' strong desire for feedback. The study advances the literature by suggesting a typology of prehospital feedback and presenting a unique insight into the motives for feedback-seeking using psychological theory. A logic model for prehospital feedback interventions was developed to inform future research and development into prehospital feedback.